2015
DOI: 10.1021/nn5057063
|View full text |Cite
|
Sign up to set email alerts
|

Magnetoresistance and Charge Transport in Graphene Governed by Nitrogen Dopants

Abstract: We identify the influence of nitrogen-doping on charge- and magnetotransport of single layer graphene by comparing doped and undoped samples. Both sample types are grown by chemical vapor deposition (CVD) and transferred in an identical process onto Si/SiO2 wafers. We characterize the samples by Raman spectroscopy as well as by variable temperature magnetotransport measurements. Over the entire temperature range, the charge transport properties of all undoped samples are in line with literature values. The nit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

7
57
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 53 publications
(67 citation statements)
references
References 47 publications
7
57
1
Order By: Relevance
“…However, defects in graphene can lower its electron mobility significantly and degrade its electron transport properties. Lattice defects such as vacancies and dopant atoms have been shown to lead to additional scattering in graphene. Moreover, mechanical deformation, bending and strain can significantly change graphene's electronic transport properties .…”
Section: Introductionmentioning
confidence: 99%
“…However, defects in graphene can lower its electron mobility significantly and degrade its electron transport properties. Lattice defects such as vacancies and dopant atoms have been shown to lead to additional scattering in graphene. Moreover, mechanical deformation, bending and strain can significantly change graphene's electronic transport properties .…”
Section: Introductionmentioning
confidence: 99%
“…The doping with heteroatoms creates charged sites in the graphene lattice, as a result the spin and charge densities are redistributed bringing new functionalities [16]. In this prospect, nitrogen incorporation in graphene by substitution of carbon atoms has been explored significantly to achieve high electron density, n-type doping, increased capacity of battery, high supercapacitance and oxygen reduction activities [16][17][18][19][20][21][22]. Thus, various studies have revealed that nitrogen doping can be exciting platform to tune or introduce novel properties in graphene.…”
Section: Introductionmentioning
confidence: 99%
“…For high fields, we observe a positive MR for undoped samples as seen by others 31,32 which here follows a B 2 -dependence. Thus, we interpret this as a classical Lorentz MR. 31 This behavior changes to negative MR for ion-implanted samples, which is for undoped samples only found for small fields. Consequently, the presence of atomic scale defects leads to this change to negative MR. Interestingly, in the case of nitrogen implantation the change is much less than for boron and carbon, which could be explained with either a different scattering potential or the absence of lattice defects.…”
mentioning
confidence: 96%